Analysis of Student Errors in Solving SPLDV Story Problems Based on Visual Learning Styles - Maria Fatima Luruk; Lailin Hijriani; Yohanes Jefrianus Kehi (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
This study aims to describe the types of errors and the factors that cause students' errors in solving SPLDV story problems from a visual learning style perspective. The type of research used is descriptive qualitative. The research subjects consisted of Class VIII at SMP Negeri 2 Malaka Barat, who were identified as having a visual learning style. The research instruments were essay tests on SPLDV word problems and interview guidelines. Students' errors were analyzed using Kastelan’s theory, which classifies errors into conceptual, procedural, and technical. The results showed that students with visual learning style still made various errors, including (1) conceptual errors, such as inability to construct mathematical models from word problems and misapplying elimination or substitution methods; (2) procedural errors, such as failing to write systematic solving steps and not completing problems until the final stage; (3) technical errors, such as miscalculations and mistakes in copying numbers or variabels. The causes of errors came from internal factors (lack of conceptual understanding, inaccuracy, and difficulty in translating verbal information into symbolic form) and external factors (teaching methods with minimal visualization, an unconducive learning environment, and limited solving time).